Can preoperative inflammatory markers predict the success of varicocelectomy?. (26th June 2022) - Duran, Mesut Berkan; Kizilkan, Yalcin; Senel, Samet; Yikilmaz, Taha Numan; Toksoz, Serdar
Abstract: The aim of this study was to evaluate the effect of inflammation on the success of varicocelectomy by using some inflammatory markers. Adult male patients aged ≥18 years who were evaluated for infertility, had abnormal parameters in at least two preoperative semen analyses and underwent subinguinal microscopic varicocelectomy were retrospectively evaluated. The patients were divided into two groups; those showing improvement in semen parameters were determined as Group A and those without improvement as Group B and compared with each other. A total of 102 patients were included in this study. Group A contained 32 (31.4%) patients while Group B had 70 (68.6%) patients. Monocyte/lymphocyte ratio (MLR) and neutrophil/lymphocyte ratio (NLR) were found to be statistically significantly higher in Group B ( p  = 0.014 and p  = 0.028 respectively). Although preoperative sperm concentration and total motile sperm count were higher in Group B, postoperative all semen parameters were significantly higher in Group A. The cutoff points that were determined using the Youden test were <2.02 for NLR (AUC = 0.636, CI = 0.519–0.754; p  = 0.028) and <0.22 for MLR (AUC = 0.652, CI = 0.531–0.773; p  = 0.014). Pre‐varicocelectomy low NLR and MLR values were found to be significant parameters in predicting the success of the surgery.